Linking the Timing of Career and Technical Education Coursetaking With High School Dropout and College-Going Behavior. (April 2018) - Gottfried, Michael A.; Plasman, Jay Stratte
While prior studies have examined the efficacy of career and technical education (CTE) courses on high school students' outcomes, there is little knowledge on timing of these courses and a potential link to student outcomes. We asked if the timing of these courses predicted differences in the likelihood of dropout and on-time high school graduation as well as college-going behaviors. We found that CTE coursetaking in high school was linked to lower chances of dropout and increased chances of on-time graduation, especially when these courses were taken later in high school. Little evidence arose that CTE coursetaking boosts college-going behaviors. The implications speak to the role of timing of CTE coursetaking, specifically on end of high school outcomes.